Exploring a career pathway for home support workers in Ireland: a systematic scoping review of the international evidence - Morrow, Elizabeth; Kelly, Carmel; Killeen, Clodagh; Naessens, Edward; Lynch, Mary (Frontiers in Health Services, 2024)
Background In prosperous nations like Ireland, home support workers (HSWs) play an increasingly vital role in providing person-centred care to ageing populations. However, challenges such as workforce shortages, role ambiguity, low pay, and limited career advancement, hinder workforce development and career building. Method A scoping review using key terms for “HSWs” and “career pathways” was conducted following the Joanna Briggs Institute Methodology, examining electronic databases (Web of Science, PubMed, MEDLINE, EMBASE, CINAHL, PscyINFO, Social Care Online, Social Sciences Citation Index). Inclusion criteria were applied, and a thematic analysis followed and inductive-deductive approach. Results The review encompassed 261 relevant articles from different countries. Four key themes were identified: (1) Data-driven decision-making on the future workforce, (2) Attracting and developing a competent and motivated home support workforce, (3) Enhancing working lives and retention at every stage of career pathways, and (4) Crafting career pathways to improve quality and impact. Discussion Leadership, collaboration, and data-driven decision-making across policy, research and practice are pivotal for expanding and enhancing home support. Emphasising a shift towards preventative self-management models, supported by digitally skilled and regulated HSWs, could enhance independence and quality of care. Clear career structures, professional development, and inclusive organisational environments are essential to attract, retain, and empower a competent and motivated workforce, fostering quality and impact. Conclusion This scoping review provides foundational evidence to establish career pathways for HSWs, identifying key areas for development such as data collection, care model transformation, career progression structures, and systems for safety and quality improvement.